Pengaruh Harga dan Media Sosial terhadap Peningkatan Volume Penjualan Perumahan Bersubsidi di Kota ParePare - Musdawina, Musdawina; Basalamah, Salim; Plyriadi, Annas (STIE AMKOP, 2024)
This research was conducted with the aim of: (1) Testing and analyzing the influence of prices on increased sales volumes; (2) Test and analyze the impact of social media on increasing sales volume. The study uses data collection techniques through observation and division of the questionnaire of 119 respondents as a sample of the total number of users of 2,984 people with the construction period of houses that have been purchased since 2019 – 2022, the study was conducted from 11 December 2023 to 11 January 2024. The data was analyzed using the WarpPLS 7.0 program. The results of this study show that: (1) Prices have a positive and significant influence on increased sales volumes; (2) Social media have a positively and significantly influenced the increase in sales volume. Keywords: Price, Social Media, Sales Volume